Bivalirudin Versus Heparin Monotherapy in ST-Segment–Elevation Myocardial Infarction. (December 2021) - James, Stefan; Koul, Sasha; Andersson, Jonas; Angerås, Oskar; Bhiladvala, Pallonji; Calais, Fredrik; Danielewicz, Mikael; Fröbert, Ole; Grimfjärd, Per; Götberg, Matthias; Henareh, Loghman; Ioanes, Dan; et al.
Abstract : Background: Bivalirudin was not superior to unfractionated heparin in patients with myocardial infarction (MI) treated with percutaneous coronary intervention and no planned use of GPI (glycoprotein IIb/IIIa inhibitors) in contemporary clinical practice of radial access and potent P2Y12 -inhibitors in the VALIDATE-SWEDEHEART randomized clinical trial (Bivalirudin Versus Heparin in STEMI and NSTEMI Patients on Modern Antiplatelet Therapy–Swedish Web-System for Enhancement and Development of Evidence-Based Care in Heart Disease Evaluated According to Recommended Therapies Registry). Methods: In this prespecified separately powered subgroup analysis, we included patients with ST-segment–elevation MI undergoing primary percutaneous coronary intervention with the primary composite end point of all-cause death, MI, or major bleeding event within 180 days. Results: Among the 6006 patients enrolled in the trial, 3005 patients with ST-segment–elevation MI were randomized to receive bivalirudin or heparin. The mean age was 66.8 years. According to protocol recommendations, 87% were treated with potent oral P2Y12 -inhibitors before start of angiography and radial access was used in 90%. GPI was used in 51 (3.4%) and 74 (4.9%) of patients randomized to receive bivalirudin and heparin, respectively. The primary end point occurred in 12.5% (187 of 1501) and 13.0% (196 of 1504; hazard ratio [HR], 0.95 [95% CI, 0.78–1.17], P =0.64) with consistent results in all major subgroups. All-cause death occurred in 3.9% versus 3.9% (HR, 1.00 [0.70–1.45], P =0.98), MI in 1.7% versus 2.2% (HR, 0.76 [0.45–1.28], P =0.30), major bleeding in 8.3% versus 8.0% (HR, 1.04 [0.81–1.33], P =0.78), and definite stent thrombosis in 0.5% versus 1.3% (HR, 0.42 [0.18–0.96], P =0.04). Conclusions: In patients with ST-segment–elevation MI undergoing primary percutaneous coronary intervention with radial access and receiving current recommended treatments with potent P2Y12 -inhibitors rate of the composite of all-cause death, MI, or major bleeding was not lower in those randomized to receive bivalirudin as compared with heparin. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02311231. Abstract : Supplemental Digital Content is available in the text.